Extraction, Characterization, and Biological Activity of Volatile and Non-volatile Components of Grapefruit - Zulifqar, Ayesha; Gillani, Syeda Shaista; Akhtar, Hafsa (Scientific Inquiry and Review, 2024)
Grapefruit (Citrus X paradisi) is among the biggest and most popular fruit crops grown for profit, worldwide. It is not only economically essential but also remains a popular human dietary ingredient. There are numerous varieties of citrus, all coming with vibrant colors. Both processed and fresh forms are consumed. Half of the fruit, including seeds, peels, and pith remnants are inedible and wasted after processing. Pectin, essential oils, citric acid, flavonoids, and other significant phytochemicals derived from citrus are currently widely studied in food, industrial, and synthetic chemistry. This study examines the properties of flavonoids derived from citrus leaves, their extraction process, and their usage with respect to potential health advantages. Using GC-MS/MS, the flavonoids content of grapefruit leaf extracts was determined. It was found that the primary flavonoid present in grapefruit pulp, oven-dried leaves, and fresh leaves was isonaringin. In new experiments, fresh and dried leaves of grapefruit (dried at 45°C) showed a potent cytoprotective effect on neuroblastomas SH-SY5Y. According to the data, bioactive flavonoids are naturally found in fruit leaves that can be used as remedy in many therapeutic and antibacterial activities.